2022
DOI: 10.1155/2022/7769355
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Protects against MPP+/MPTP-Induced Dopaminergic Neuron Death in Parkinson’s Disease by Inhibiting Ferroptosis

Abstract: Ferroptosis, a novel form of regulated cell death, is caused by accumulation of lipid peroxides and excessive iron deposition. This process has been linked to the death of dopaminergic neurons in substantia nigra compacta (SNc) of Parkinson’s disease (PD) patients. Quercetin (QCT), a natural flavonoid, has multiple pharmacological activities. However, it has not been established whether QCT can protect against dopaminergic neuron death by inhibiting ferroptosis. In this study, we investigated the potential ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…By controlling the Nrf2-mediated ferroptosis pathway, quercetin also lessens the symptoms of seizures by kainate [49]. Numerous studies have also demonstrated that quercetin, a ferroptosis inhibitor, provides a new therapeutic strategy for ferroptosis-related diseases [50,51]. In addition to the encouraging outcomes of the molecular docking tests, earlier research has shown the importance of this molecular docking investigation.…”
Section: Discussionmentioning
confidence: 97%
“…By controlling the Nrf2-mediated ferroptosis pathway, quercetin also lessens the symptoms of seizures by kainate [49]. Numerous studies have also demonstrated that quercetin, a ferroptosis inhibitor, provides a new therapeutic strategy for ferroptosis-related diseases [50,51]. In addition to the encouraging outcomes of the molecular docking tests, earlier research has shown the importance of this molecular docking investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Lin et al demonstrated that the substantia nigra of MPTP-induced Parkinson’s disease (PD) mice showed ferroptosis-related biochemical features, with high levels of MDA and low levels of superoxide dismutase (SOD) and GSH, indicating that ferroptosis was involved in the development of PD . Importantly, quercetin could up-regulate the expression of the downstream genes SLC7A11 and GPX4 by activating NRF2, thereby inhibiting lipid peroxidation in dopaminergic neurons . Icariside II, a flavonol glycoside derived from Epimedium koreanum , could suppress the expression of GPX4 via up-regulating miR-324-3p and thus promoted ferroptosis in renal cell carcinoma cells, indicating that icariside II might be used as an adjuvant therapy for renal cancer .…”
Section: Natural Flavonoids Targeting Ferroptosismentioning
confidence: 99%
“…In-depth studies found that this compound alleviated the morphological changes and lipid peroxidation through activating the Sirtuin 1 (SIRT1)/NRF2/SLC7A11/GPX4 pathway, thus exerting neuroprotective effects. Lin et al demonstrated that the substantia nigra of MPTP-induced Parkinson’s disease (PD) mice showed ferroptosis-related biochemical features, with high levels of MDA and low levels of superoxide dismutase (SOD) and GSH, indicating that ferroptosis was involved in the development of PD . Importantly, quercetin could up-regulate the expression of the downstream genes SLC7A11 and GPX4 by activating NRF2, thereby inhibiting lipid peroxidation in dopaminergic neurons .…”
Section: Natural Flavonoids Targeting Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin has been shown to prevent the activation of the neuron’s ferroptosis pathway by chelating reduced iron and increasing the expression of the glutathione peroxidase [ 90 ]. The subsequent increase of Nrf2 expression in neurons by quercetin can upregulate the expression of glutathione peroxidase 4 and SLCA11 enzymes that prevent the production of lipid radicals that are the product of iron toxicity [ 91 ].…”
Section: Quercetinmentioning
confidence: 99%